HALP score as a prognostic marker for overall survival in advanced pancreatic cancer - Demir, Nazan; Gökmen, İvo; Sağdıç Karateke, Yasemin; İlhan, Ayşegül; Yıldız, Fatih; Bayır Garbioğlu, Duygu; Yıldız, Bülent (Frontiers in Oncology, 2025)
IntroductionPancreatic cancer is the leading cause of cancer-related deaths worldwide and most of the patients diagnosed at an advanced stage. Clinicians need simple, effective, and repeatable tools to predict the prognosis. This study aimed to evaluate the relationship between the HALP score and prognosis in patients with advanced pancreatic cancer.MethodsPatients diagnosed with advanced pancreatic cancer at three centers in Turkey between 2009 and 2023 were included in this retrospective study. Demographic features, blood parameters, treatment received, treatment responses, and survival were recorded.Results227 patients were included in the study. The median overall survival (OS) for the entire cohort was 10.4 months. The median OS was 8.7 months in the low-HALP group and 11.2 months in the high- HALP group. Patients in the low-HALP group had a significantly shorter median OS than those in the high-HALP group (log rank p=0.001).ConclusionThe HALP score is a reliable and practical tool that can be utilized in clinical practice to predict prognosis in patients with advanced pancreatic cancer.